Electrospun Silk Fibroin/Cyclodextrin Nanofibers for Multifunctional Air Filtration - Papimol Mongyun; Sompit Wanwong (Fibers)
Particulate matter (PM) and volatile organic compounds (VOCs) are major air pollutants that can cause significant risks to public health. To mitigate exposure, fibrous filters have been widely utilized for air purification. In this study, we developed electrospun silk fibroin/poly (ethylene oxide)/cyclodextrin (SF/PEO/CD) nanofibers as multifunctional air filters capable of efficiently reducing PM2.5 and degrading VOCs. The resulting SF/PEO/10CD demonstrated the best multifunctional filtration performance, achieving PM2.5 capture efficiencies of 91.3% with a minimal pressure drop of 4 Pa and VOC removal efficiency of 50%. These characteristics highlight the potential of the SF/PEO/10CD nanofiber with effective, multifunctional properties and environmental benefits for sustainable air filtration application.